KAJIAN KEPUASAN MASYARAKAT PENGHAYAT KEPERCAYAAN TERHADAP PELAYANAN DOKUMEN KEPENDUDUKAN DI KABUPATEN BREBES - Ahmad Fatkul Fikri; Titisari Haruming Tyas (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2021)
The faith's adherents often get discriminated against in the service of population documents. Believers are required to fill in one of the official religions in Indonesia. The presence of the Decision of the Constitutional Court Number 97/PUU-XIV/2016 could not eliminate the act of discrimination. The state cannot guarantee the continuity of religion and belief that its adherents believe as guaranteed by the state constitution. This study aims to determine the Community Satisfaction Index (IKM) adherents of faith in the service of population documents in Brebes Regency with a quantitative descriptive approach. The sampling technique used is purposive sampling with data collection techniques of observation, documentation, and questionnaires. This research used Pearson's Product Moment validity test and Cronbach's alpha formula for reliability test to determine the questionnaire questions' validity. The study results show that the Community Satisfaction Index (IKM) of adherents' belief in services at the Population and Civil Registration Office of Brebes Regency is 2.83, with a conversion value of 70.75. So the performance of public services is of good quality. However, there are still service indicators in the poor category, namely equal rights and equal treatment/non-discrimination.